Recent advances in heterometallic polyoxotitanium clusters - Liu, Ya-Jie; Fang, Wei-Hui; Zhang, Lei; Zhang, Jian (Coordination chemistry reviews, 2020)
•Clear definition and specific classification for atomically precise HPTCs are provided.•Typical examples are illustrated from synthesis-structures-properties perspective.•Bright future for HPTCs in bottom-up assembly for materials with tunable performances. To exploit the use of solar energy in photocatalysis, metal ion doping is one of the most effective ways. At present, atomically precise heterometallic polyoxotitanium clusters (HPTCs) are of great interest as well-defined models for the way in which metal ions are doped into bulk titanium dioxide. Recently, researchers have contributed great efforts in HPTCs where majority metal ions throughout the periodic table have successfully incorporated. The incorporation of particular characteristics of metal dopants provides the opportunity to modify the microscopic electronic structure, then optical response, and ultimate macroscopical performances. In this review, we aim to summarize the recent progress on such a rapidly evolving topic of HPTCs and provide potential theoretical models for the rational design of photocatalysts and solar energy capture. Firstly, a brief summary of the synthetic strategies and bonding models between the metals and PTCs is provided. Then clear definition and classification of the HPTCs reported up to date is given. Moreover, representative examples are illustrated from experimental, theoretical and photophysical/photochemical perspectives, particularly in light absorption, fluorescence, photocatalysis, and gas sorption etc. Finally, the main challenges and opportunities are proposed with the goal of expanding the sunlight harvesting application range of HPTCs.